Mossbauer analysis of the f.c.c. Fe-Ni-C alloys structure after heat and ultrasonic treatments - Nadutov, V.M.; Semenov, D.V.; Svystunov, Ye.O.; Kuzmich, G.I. (Functional Materials, 2004)
Mossbauer spectroscopy has been used for atomic scale investigation of austenitic Fe-Ni-C alloys after ultrasonic and low-frequency impact surface treatments. The phase composition and hyperfine structure of the Fe-30.5 % Ni—1.5 %C and Fe-25.3 %Ni-0.78 %C alloys with the f.c.c. lattice after annealing at 1373 K and 773 K in vacuum and following ultrasonic surface treatment (UST, f = 1—3 kHz, the amplitude 20 pm, t = 8— 24 s) have been studied. The results were analyzed in comparison with the low-frequency impact surface treatment (1ST) of the alloys. The microhardness of the alloys after UST has been analyzed.